Southeast Asian food security one year into the Ukraine war - Donnellon-May, Genevieve (2023)
Since the outbreak of war between Russia and Ukraine more than a year ago, supply chains of food and fertiliser from the two countries have been disrupted and food insecurity of many countries heightened. Southeast Asia has weathered the overall impact of the war relatively well. Although the region has witnessed short-term food shortages and price hikes, neither widespread food insecurity nor mass hunger has visibly increased. As the prospect of a prolonged conflict continues, governments must now consider implementing longer-term measures to help safeguard their domestic food security.